A novel anti-epileptogenesis strategy of temporal lobe epilepsy based on nitric oxide donor - Xian-Hui Zhu; Ya-Ping Zhou; Qiao Zhang; Ming-Yi Zhu; Xiao-Wei Song; Jun Li; Jiang Chen; Yun Shi; Kang-Jian Sun; Yong-Jie Zhang; Jing Zhang; Tian Xia; et al. (EMBO Molecular Medicine)
Abstract The molecular mechanism underlying the role of hippocampal hilar interneuron degeneration in temporal lobe epilepsy (TLE) remains unclear. Especially, very few studies have focused on the role of neuronal nitric oxide synthase (nNOS, encoded by Nos1) containing hilar interneurons in TLE. In the present study, Nos1 conditional knockout mice were constructed, and we found that selective deletion of Nos1 in hilar interneurons rather than dentate granular cells (DGCs) triggered epileptogenesis. The level of nNOS was downregulated in patients and mice with TLE. Nos1 deletion led to excessive epilepsy-like excitatory input circuit formation and hyperexcitation of DGCs. Replenishment of hilar nNOS protein blocked epileptogenic development and memory impairment in pilocarpine-induced TLE mice. Moreover, chronic treatment with DETA/NONOate, a slowly released exogenous nitric oxide (NO) donor, prevented aberrant neural circuits of DGCs and the consequent epileptogenesis without acute antiseizure effects. Therefore, we concluded that NO donor therapy may be a novel anti-epileptogenesis strategy, different from existing antiseizure medications (ASMs), for curing TLE.